Avaliação da produção de sedimentos em eventos chuvosos na bacia experimental de São Martinho da Serra - Sangoi, Raniere Gustavo (2007)
The intense use of the soil and natural resources emphasizes the importance of researching fields related to sediment transport and sediment deposition in catchments. Consequently sediment yield is object of concern in situations regarding the land se and water resources management. The main objective of this research was to evaluate the sediment yield at Sao Martinho da Serra experimental catchment (region named Lajeado Grande). Such evaluation was accomplished by monitoring the water resources in the specific region. The field methodology included liquid discharges measurements, rainfall data collection, suspended sediment and bed material sampling, included tests to determine suspended sediment concentration and particle size distribution for the suspended and bed material. Sediment and flow rating curves were produced to the specific catchment. The largest possible number of rainfall events was monitored during the research period (23/12/2005 a 15/06/2007). The water level and the discharge measurements were carried out upstream and downstream to the studying area. Rainfall data were obtained from the rain gauge installed next to the area. Six methods were applied to calculate the sediment yield during rainfall events. Such methods were chosen according the measured data availabilty. The best adjust between sediment yield measured and calculated values was obtained with the application of MUSLE, which was applied by sub-catchments and relates the sediment yield to the observed effective rainfall (Hef).